Pengaruh Pelatihan Kerja Terhadap Kinerja Karyawan PT. Perawang Sukses Perkasa Industri Distrik Petapahan - Hendra, Teguh; Anuar, Saiful (Eko dan Bisnis: Riau Economic and Business Review, 2023)
One of the resources that can affect the maximum or not in achieving organizational goals in order to get good work results is the human being or the employee himself, so of course employees who are reliable or have good work abilities are needed. Good ability can be seen from the expertise of each employee, knowledge or insight possessed and attitude or behavior in the daily life of a person carrying out and completing a job. This study aims to determine the effect of job training on employee performance. The number of samples in this study were 39 people. The results of this study indicate that from the results of the overall validity test the statement items of job training and performance variables are stated to be valid because the value of rcount > rtable (0.316) is obtained. The results of a simple linear regression test obtained a value of Y = 12,811 + 0.528X. From the results of the hypothesis testing on the t test results, the tcount value (4.085) is greater than the ttable value (2.02619) with a significant level of 0.000 <0.05, which means that job training has an effect on performance. And from the test results of the coefficient of determination (R2) a value of 0.311 is obtained, meaning that the contribution or magnitude of the influence of job training on performance is 0.311 or 31.1% while the remaining 68.9% is influenced by other variables which are ignored or not examined in this study.